Frequency of Pneumocystis jirovecii in sputum from HIV and TB patients in Namibia - Vincent Nowaseb; Esegiel Gaeb; Marcin G Fraczek; Malcolm D Richardson; David W Denning (Journal of Infection in Developing Countries)
Introduction: The opportunistic fungus Pneumocystis jirovecii causes Pneumocystis pneumonia (PcP), which is a life-threatening infection in HIV/AIDS patients. The seemingly low prevalence of P. jirovecii pneumonia in sub-Saharan Africa has been a matter of great debate because many HIV/AIDS patients reside in this region. The lack of suitable diagnostic practices in this resource limited-region has been added to the uncertainty of PcP prevalence. Only a few studies have evaluated the utility of easily obtainable samples such as expectorated sputum for diagnosis of PcP. Thus, the aim of the current study was to evaluate the effectiveness of expectorated sputum for the routine diagnosis of PcP in a resource-limited sub-Saharan African setting. Methodology: Randomly collected sputum samples were analysed by microscopy after Grocott’s methenamine silver (GMS) stain staining and by qPCR to determine the minimum frequency of detectable P. jirovecii. Results: A total of 475 samples were analysed. Twenty five (5.3%) samples were positive for P. jirovecii, i.e., 17 (3.6%) using both qPCR and GMS staining and eight (1.7%) using qPCR only. P. jirovecii was present in 8/150 (5.3%) HIV-positive and tuberculosis (TB) smear-negative patients, and in 12/227 (5.3%) TB smear-negative patients with an unknown HIV status. The minimum frequency of PcP was 3.6% in Namibian HIV and TB patients, while the actual frequency is likely to be 5.3%. Conclusion: This study demonstrated that expectorated sputum can be used routinely for the diagnosis of PcP by GMS, although qPCR is more sensitive, and it requires less time and skill.